Hematopoietic stem cell transplantation in Puebla, México. Traveled roadand goals achieved - Limon Flores, José Alejandro; Pérez Lozano, Uendy; Solis Poblano, Juan Carlos; Terán Cerqueda, Vanessa; López Marthen, Jorge Luis; Sarmiento Candelaria, Gabriela; Vera Villicaña, Cindy Trinidad; Gutierrez Gurrola, Balbina; Herrera Madrid, Diana Arleth; Balan Ortiz, Vanessa; Vazquez Gutierrez, Liliana; Morales López, Elizabeth; et al. (Revista Cubana de Hematología, Inmunología y Hemoterapia, 2017)
Introduction: In México there are only 4 cities that have significantly active hematopoietic stem cell transplantation programs; onlyin 3 of those cities, the most important national public health institution IMSS (Mexican Social Security Institute) count with them. The cities where these programs are found are Mexico City, Monterrey and Puebla. Since the beginning of this decade, and before, the productivity of these transplant programs in this public health institution is low, performing on average 148 transplants every year. Results: In the span comprised between April 1995 and October 2016, we have performed 474 hematopoietic transplants in our hospital; 229 of them were allogeneic and 245 autologous, in adult and children population. This accumulated experience has allowed the implementation of all the variety of hematopoietic stem cell transplantation available in our country, this has opened up the opportunity, for the first time in our institution, the possibility to provide a donor for every patient who requires an hematopoietic transplant, overcoming the phase in which patients could not be submitted to the procedure for lack of a compatible donor. Conclusions: The goals achieved in our hospital confirm the feasibility in developing uninterrupted long term transplant programs in hospitals not specially equipped with technology nor abundant funds of the public health system in the national province, and it shows that this programs can be created and developed in hospitals with similar conditions to ours in México, Latin America and middle-low income countries.